Use of natural pigments obtained from cyanobacteria and algae - Alina Trofim; Anastasia Verdeș (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
The article reflects data on the use of cyanobacteria pigments in cosmetology. One of the sources of natural antioxidants are the pigments obtained from various algae and cyanobacteria. An essential source for extracting pigments and biologically active substances used in cosmetology, pharmaceuticals, etc. is represented by algae and cyanobacteria. Also, the extracts from cyanobacteria have an important role in the anti-wrinkle effect. Useful pigments include: carotenoids, xanthophylls, astaxanthin, fucoxanthin, chlorophyll, phycoerythrin.